Admiring Max Johnson's motor boat, Haystack (1955)
Last motor boat built in Haystack, ready for launch. Includes Clayton Halfyard, Oakley Johnson, William Tulk, Alfred Jarvis, Wilber Allen and Albert Paul. This collection contains copies made in 1998 of original photographs gathered by the Haystack Reunion Committee for publication in their booklet Haystack Reflections (1997).